1988
DOI: 10.1093/oxfordjournals.aje.a114780
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Self-Administered Questionnaire to Assess Diet Four Years in the Past

Abstract: The use of a mailed, self-administered, semiquantitative food frequency questionnaire to describe past dietary intake was evaluated in 1984 among a group of 150 Boston-area women who had completed four one-week diet records three to four years previously. Correlation coefficients comparing calorie-adjusted nutrient intakes computed from the questionnaire with those obtained from a compressed version of the questionnaire completed during diet record keeping ranged from 0.44 for total carbohydrate to 0.62 for vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
414
3
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 731 publications
(439 citation statements)
references
References 0 publications
9
414
3
8
Order By: Relevance
“…In many studies, the validity of dietary assessments ranging from 3-10 years has seen strong correlations with the reference, generally in the range of 0.5-0.7. 19,20,21 Overall, studies have suggested that diet may be recalled with acceptable levels of misclassification up to approximately 10 years. Considering that most of the GC patients in our study were older persons, it was thought that the usual diet for 12-months of 3 years prior to cancer diagnosis was valid.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the validity of dietary assessments ranging from 3-10 years has seen strong correlations with the reference, generally in the range of 0.5-0.7. 19,20,21 Overall, studies have suggested that diet may be recalled with acceptable levels of misclassification up to approximately 10 years. Considering that most of the GC patients in our study were older persons, it was thought that the usual diet for 12-months of 3 years prior to cancer diagnosis was valid.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with several versions of the Willett FFQ and the UK-EPIC FFQ that were repeatadministered at least 6 months apart in free-living adults, the current FFQ provided highly comparable reliability coefficients for most nutrients (12,29,31,32,(34)(35)(36)(37)(38) . For vitamin C, our FFQ appeared to be more reliable than various forms of the Willett FFQ (29,31,32,(34)(35)(36)38) and showed similar reliability to the UK-EPIC FFQ (37) . These results indicate that a single administration of the FFQ is sufficient to provide nutrient measures with a high level of reliability.…”
Section: Test-retest Reliabilitymentioning
confidence: 95%
“…13 Nutrient intake was computed by multiplying the frequency response by the nutrient content of the specified portion sizes. Heme iron content was calculated by applying a factor of 0.4 to the total iron content of all meat items, as proposed by Monsen.…”
Section: Methodsmentioning
confidence: 99%